Design modifications of a UAV wing for optimal integration of a magnetic anomaly detection sensor - Gameiro, Gonçalo (Academia da Força Aérea; Instituto Superior Técnico, 2018)
This work describes the conceptual design of a Unmanned Air Vehicle (UAV) wing with a Magnetic Anomaly Detection (MAD) sensor for submarine detection operations. Nowadays, underwater marine vessels are able to evade conventional detection methods such as sonar. Therefore, it is necessary to integrate MAD sensors in modern Anti-Submarine Warfare theatres. UAVs typically generate a magnetic field due to the electrical systems on board, causing interference noise on the MAD sensor data analysis and compromising its performance. To address these issues, a characterization of the aircraft’s magnetic signature was conducted, and it was found that the wing tip and a tail stinger boom are the best options to minimize the magnetic noise. A structural and aerodynamic analysis of the aircraft showed the wing tip configuration was the best option since the amount of mass required to counter the moment of a tail stinger boom would require major modifications on the UAV. Also, the aircraft magnetic signature is minimum at the wing tip, with an intensity of -2.9nT. An aerodynamic characterization of the aircraft was carried to evaluate the effect of the MAD pods on the wingtips. A parametric optimization of the wing was conducted. Given the dimensional constraints on the wing structure and a target magnetic noise of 2nT at the wing tip, the optimizer objective function was to minimize the total fuel consumption. The optimum solution allowed a decrease of 30% on the magnetic noise and a fuel consumption of 8.71 kg of fuel for an 8-hour search operation.

Este trabalho descreve o processo de projeto conceptual de uma asa de um Veículo Aéreo Não-Tripulado (VANT) com um sensor de anomalias magnéticas (AM) para ser usado em deteção de submarinos. Atualmente, estes veículos estão dotados com capacidades que diminuem as hipóteses de detecão por métodos convencionais, como o sonar. Assim, torna-se necessário integrar sensores de AM em cenários atuais de Guerra Anti-Submarina. Os sistemas aviónicos destas aeronaves geram um campo magnético que causa interferência no sensor de AM, causando ruído nos dados da análise e comprometendo a sua eficiência. Para evitar este problema, realizou-se uma caracterização da assinatura magnética da aeronave, concluindo que as pontas das asas e uma configuração de arpão na cauda seriam as melhores soluções para colocar o sensor, a fim de minimizar a interferência magnética. Estudos estruturais e aerodinâmicos revelaram que a primeira seria a melhor opção, pois a massa necessária para anular o momento gerado na segunda requeria alterações substanciais na estrutura da aeronave. A ponta da asa era também o local com menor nível de assinatura magnética. Realizou-se uma otimização paramétrica da asa da aeronave, considerando os efeitos aerodinâmicos dos invólucros do sensor. Atendendo às restrições no dimensionamento da estrutura da asa e a um valor de interferência magnética, o otimizador teria como objetivo minimizar o consumo total de combustível. A solução ótima permitiu reduzir em 30% o valor da assinatura magnética na ponta da asa e obter uma configuração que, numa missão de patrulha de 8 horas, consome 8.71 kg de combustível.
Supervisors: Prof. Afzal Suleman. Examination Committee: Chairperson: Prof. Filipe Szolnoky Ramos Pinto Cunha; Supervisor: Prof. Afzal Suleman; Member of the Committee: Major Dr. Luís Filipe da Silva Félix
Keywords: Aircraft design; Unmanned aerial vehicle; Anti-submarine warfare; Magnetic anomaly detection sensor; Parametric optimization; Projeto de aeronaves; Veículo aéreo não-tripulado; Guerra anti-submarina; Sensor de anomalias magnéticas; Otimização paramétrica